Pengembangan Media Pembelajaran Komik Fisika Berbasis Integrasi-Interkoneksi Nilai-Nilai Alquran (UPEJ Unnes Physics Education Journal, 2017)
Using of powerpoint in learning still displays a lot of text, so it minimize its legibility and students feel difficult to understand the concepts of Physics. Therefore it needs an effective media for students, that is comic. This research aims to determine the characteristics, appropriateness, responses of students, and the effectiveness of developed comic media. The method used to achieve the goal is research and development method. The developed comic media has four characteristics, those are having islamic nuance, giving dynamic fluid material connected to Quran verses, giving characters values based on Quran, and there are page, which, tell about the characteristics of Prophet Muhammad SAW, Aisha r.a., and Sultan Fatah. The Comic media was stated appropriate as media by material expert and media expert. Students' responses to the media are very good because the comic is easier and more interesting to be understood than the book used.